Functioning of Young Adults With ADHD in the Military. Issue 12 (October 2019) - Fruchter, Eyal; Marom-Harel, Hadar; Fenchel, Daphna; Kapra, Ori; Ginat, Keren; Portuguese, Shirley; Weiser, Mark
Objective: To assess the functioning of young adults with ADHD in a military setting.Method: In all, 14, 655 young adults with ADHD (mean age at first examination 17.8 ± 0.7) attending mandatory service in the Israeli military were compared with matched controls on several functioning domains.Results: Young adults with ADHD had more sessions with mental health care professionals, physician appointments, sick days, and disqualifications of professions than controls ( p < .001). Young adults with ADHD were also less medically fit for combat service (odds ratio [OR] = 0.75, 95% confidence interval [CI] = [0.72, 0.79]), more medically unfit for military service in general (OR = 1.26, 95% CI = [1.13, 1.40]), and had higher rates of overweight and obesity ( p < .001). In addition, they were more likely to be diagnosed with a personality disorder (OR = 1.29, 95% CI = [1.07, 1.53]) or with minor affective and anxiety disorders (OR = 1.33, 95% CI = [1.06, 1.67]) than matched controls.Conclusion: These results support a negative effect of ADHD on the functioning of young adults in a military setting.